Formation of Mixed Ligand Complexes of UO Involving Some Nitrogen and Oxygen Donor Ligands - Singh, Mamta; Nayan, Ram (Asian Journal of Chemistry, 2010)
The complexation reactions of UO22+ ion with nitrogen and oxygen donor ligands, 1-amino-2-naphthol-4-sulphonic acid, o-aminophenol (ap), 2-hydroxybenzoic acid (sa), 3-carboxy-4-hydroxybenzenesulphonic acid (ss) and 1,2-dihydroxybenzene (ca) have been investigated in aqueous solution employing the pH-titration technique. Aanalysis of the experimental data recorded at 25°C and at an ionic strength of 0.10 M KNO3 indicates formation of binary, hydroxo and ternary complexes including UO2(an), UO2(an)22-, UO2(an)(OH)-, UO2(ap)+, UO2(ap)2, UO2(sa), UO2(sa)22-, UO2(sa)(OH)-, UO2(sa2)(OH)3-, UO2(ss), UO(ss)24 -, UO(ss)(OH)2-, UO2(ss2)(OH)5-, UO2(ca), UO2(ca)22-, UO2(ca)(OH)-, UO2(an)(ap)-, UO2(an)(sa)2-, UO2(an)(ss)3-, UO2(an)(ca)2-, UO2(ap)(sa)-, UO2(ap)(ss)2-, UO2(ap)(ca)-, UO2(sa)(ss)3-, UO2(sa)(ca)2-, and UO2(ss)(ca)3- in mixtures containing corresponding metal-ligand pair of ligand ratio. Formation constant values of the existing species have been evaluated and the results have been discussed.